Europe as the western peninsula of greater Eurasia geoeconomic regions in a multipolar world - Diesen, Glenn (Rowman & Littlefield, 2021)
"This book examines how the EU as a geoeconomic region will be impacted by the Russian-Chinese cooperation to construct a Greater Eurasia"--